2016
DOI: 10.1103/physrevb.94.035139
|View full text |Cite
|
Sign up to set email alerts
|

Correlated electronic properties of some graphene nanoribbons: A DMRG study

Abstract: The significant electron-electron interactions that characterize the π-electrons of graphene nanoribbons (GNRs) necessitate going beyond one-electron tight-binding description. Existing theories of electron-electron interactions in GNRs take into account one electron-one hole interactions accurately but miss higher order effects. We report highly accurate density matrix renormalization group (DMRG) calculations of the ground state electronic structure, the relative energies of the lowest one-photon versus two-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…In our case, the a priori value of the quantum information loss was set to χ = 10 −4 and the truncation errors were in the order of 10 −6 . This threshold value required block states about 15000-20000 so that, our results are far more accurate than those from previous investigations, [24][25][26] in terms of the truncation procedure. Such a large number of block states is necessary to obtain accurate gap values and correlation functions.…”
Section: Methodssupporting
confidence: 49%
See 2 more Smart Citations
“…In our case, the a priori value of the quantum information loss was set to χ = 10 −4 and the truncation errors were in the order of 10 −6 . This threshold value required block states about 15000-20000 so that, our results are far more accurate than those from previous investigations, [24][25][26] in terms of the truncation procedure. Such a large number of block states is necessary to obtain accurate gap values and correlation functions.…”
Section: Methodssupporting
confidence: 49%
“…The QMC studies mainly focused on the correlation between edge atoms and dynamical properties, 22 and the previous DMRG model calculations were restricted to very small systems. 24,26 In the widespread use of mean-field theory, it is important to investigate its reliability by examining the role of enhanced quantum fluctuations, which this approximation neglects. Although a benchmark of mean-field theory was performed for quantum dot-like structures, 21 less is known about the case of zigzag nanoribbons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ab initio DMRG calculations for neutral systems employing molecular orbitals have bottlenecks since the calculation of two-electron integrals is computationally expensive, and consequently, these studies employ ∼50 active space orbitals [ 55 ]. On the other hand, DMRG calculations with localized orbitals have been successfully employed for -conjugated systems with several hundred orbitals within the PPP Hamiltonian [ 53 , 56 , 57 , 58 , 59 ]. The ab initio study of arenes using the DMRG method has also revealed that fully-localized orbitals bring about faster convergence of energies compared to canonical Hartree–Fock orbitals or split-localized orbitals [ 55 ], making the localized description the picture of choice.…”
Section: Methodsmentioning
confidence: 99%
“…The study of these large finite graphene analogues is expected to shed light on the properties in the thermodynamic limit and the effect of electronic correlation in these industrially important two-dimensional systems. Most of the earlier studies on graphene and graphene analogues have been done within a non-interacting model or employing the restricted configuration interaction technique with a few frontier molecular orbitals [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], while the importance of electron correlation in the electronic and magnetic structures of these systems has been emphasized in recent studies [ 23 , 24 , 52 , 53 ]. In the present paper, we demonstrate the application of the symmetrized DMRG technique in the study of a graphene nanoflake, coronene, within a long-range correlated -electron model.…”
Section: Introductionmentioning
confidence: 99%